Free and bound phenolic profiles and antioxidant ability of eleven marine macroalgae from the South China Sea - Peng, Ziting; Wu, Yujiao; Fu, Qiongyao; Xiao, Juan (Frontiers in Nutrition, 2024)
Marine macroalgae are of broad interest because of their abundant bioactive phenolic compounds. However, only a few previous studies have focused on bound phenolic compounds. In this study, there were significant differences in total phenolic content, total phlorotannin content, total flavonoid content, and antioxidant ability in free and bound forms, as well as in their bound-to-free ratios, among 11 marine macroalgal species from the South China Sea. Padina gymnospora had the highest total phenolic content of free fractions, and total phlorotannin content, total flavonoid content, and antioxidant activity of free fractions. Sargassum thunbergii had the highest total phlorotannin content of bound fractions, whereas Sargassum oligocystum had the highest total flavonoid content and total phenolic content of bound fractions. Moreover, 15 phenolic acids, 35 flavonoids, 2 stilbenes, 3 bromophenols, and 3 phlorotannins were characterized and quantified using ultra-high-performance liquid chromatography with Xevo triple quadrupole mass spectrometry, and 42 phenolic compounds were reported in the bound fractions of seaweeds for the first time. Among the species, the number and amount of free and bound phenolic compounds varied greatly and the main components were different. Padina gymnospora had the largest total phenolic number, while Turbinaria ornata showed the highest total phenolic amount. Coutaric acid and diosmetin were dominant in Sargassum polycystum, and hinokiflavone was dominant in Caulerpa lentillifera, and cyanidin was dominant in the other seaweeds. Hierarchical cluster analysis was used to divide the seaweed species into seven groups. This study revealed that Padina gymnospora, Sargassum thunbergii, Turbinaria ornata, and Sargassum oligocystum are promising functional food resources.